Polysaccharide based hybrid materials : metals and metal oxides, graphene and carbon nanotubes /: metals and metal oxides, graphene and carbon nanotubes. (2018) - Vilela, Carla; Pinto, Ricardo João Borges; Pinto, Susana; Marques, Paula; Silvestre, Armando; Barros, Carmen Sofia da Rocha Freire
No abstract available